2010
DOI: 10.1002/pbc.22782
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and blood pressure changes over the course of treatment of pediatric acute lymphoblastic leukemia

Abstract: Background Obesity and hypertension are reported among survivors of pediatric acute lymphoblastic leukemia (ALL). However, little is known about the trajectory of body mass index (BMI) and blood pressure over the course of ALL therapy. Procedure In a retrospective cohort of 183 pediatric ALL patients diagnosed from 2000-2008, prevalence, severity, and risk factors for obesity and hypertension were assessed during treatment. Results At diagnosis, 36% of patients were overweight and 19% were obese. Median BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
81
4
12

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(112 citation statements)
references
References 23 publications
15
81
4
12
Order By: Relevance
“…These survivors had completed treatment within 10 years at the time of study evaluation. 8,12,13,16,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Only 2 studies 14,40 examined BMI z score assessed $10 years after the completion of treatment (ie, off treatment $10 years). Because neither study reported SD/SE of the BMI z score, the meta-analysis did not include survivors who were off treatment beyond 10 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These survivors had completed treatment within 10 years at the time of study evaluation. 8,12,13,16,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Only 2 studies 14,40 examined BMI z score assessed $10 years after the completion of treatment (ie, off treatment $10 years). Because neither study reported SD/SE of the BMI z score, the meta-analysis did not include survivors who were off treatment beyond 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…36 Ten studies explicitly reported the SD/SE of the BMI z score. For the remaining 10 studies, the SD was either calculated as a pooled SD based on subgroup values assuming equal variance (n = 5), 29,33,34,37,38 calculated from the 95% CI (n = 2), 16,27 estimated from median and range (n = 1), 39 obtained directly from study authors (n = 1), 30 or estimated based on the SD at diagnosis and SD for the change in BMI z score from diagnosis to study evaluation (n = 1). 36 To explore the association between patient and treatment characteristics and obesity, we performed subgroup meta-analyses separately by receipt of CRT, gender, and interval since treatment completion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resultados diferentes foram obtidos por outros autores 23,27 . 27 , em estudo de coorte retrospectivo realizado com 183 pacientes pediátricos com LLA, encontraram que a média de IMC aumentou durante a fase de indução da remissão da doença, com retorno para os valores normais logo após o término dessa fase.…”
Section: I S C U S S ã Ounclassified
“…27 , em estudo de coorte retrospectivo realizado com 183 pacientes pediátricos com LLA, encontraram que a média de IMC aumentou durante a fase de indução da remissão da doença, com retorno para os valores normais logo após o término dessa fase. Entretanto, houve novamente aumento do IMC nos primeiros 22 meses na fase de manutenção da terapia.…”
Section: I S C U S S ã Ounclassified